Model Predictive Control for the Reduction of DC-link Current Ripple in Two-level Three-phase Voltage Source Inverters - Xu, Junzhong; Gao, Fei; Soeiro, Thiago Batista; Chen, Linglin; Tarisciotti, Luca; Tang, Houjun; Bauer, Pavol (2020 22nd European Conference on Power Electronics and Applications (EPE'20 ECCE Europe), 2020)
In the applications of three-phase two-level voltage source inverters (VSIs) relatively large energy storage capacitors are used to absorb the high DC-link current ripples mainly caused by the circulating reactive power, the switched AC phase current flowing to the DC-link, and other dynamic and/or asymmetric operating conditions. Especially for electrolytic capacitor technology the typically high current stress and consequent losses is known to limit the power electronics lifetime, thus the design and selection of this component is critical for the whole system. To alleviate this problem, a new model predictive control (MPC) cost function which enables DC-link capacitor current ripple reduction is proposed in this paper. Based on the DC-link current mathematical model and the available VSI switching states, the future DC current ripple can be predicted, and then the optimized space vectors that best tracks the sinusoidal output current and minimizes the DC-link current ripple are chosen. Compared with conventional DC-link capacitor current reduction methods, the proposed approach has the advantage to incorporate an outstanding fast current control dynamics as well as being of relatively simple implementation because there is no need to adjust the switching signals or space vectors in the modulation as function of operational conditions of the system. Simulation and experimental results are presented verifying the effectiveness of the proposed MPC method.